Wear of zirconia-dispersed alumina at ambient temperature, 140C and 250C - Carter, Geoffrey; Van Riessen, Arie; Hart, Robert (Elsevier Science, 2006)
Commercial grade alumina along with 5, 10, 15 and 20 wt% zirconia dispersed aluminas were tested for their wear resistance at ambient temperature, 140oC and 250oC using a pin on disk tribotester fitted with a hot stage. The sample suite was investigated for physical characteristics including hardness, fracture toughness, bulk density, alumina grain size and zirconia grain size. The wear track and wear debris were investigated using profilometry, SEM as well as TEM.The 5 wt% zirconia dispersed aluminas had the lowest wear volume loss over the temperature range. The alumina sample exhibited a wear dependence with relative humidity which is attributed to the formation of a tribochemical layer. Investigation of the tribochemical layer using SEM/EDS and TEM electron diffraction showed the tribochemical layer to be aluminium hydroxide. The major wear mechanism for all samples was brittle fracture.